Perancangan Sistem Pendataan Pegawai PT PLN (Persero) UP3 Binjai Berbasis Web - Hasibuan, Inneke Nugroho; Samsudin, Samsudin (Universitas Multi Data Palembang, 2024)
As a state-owned company operating in the electricity sector, PT PLN (Persero) is committed to providing the best electricity services and meeting internationally acceptable electricity standards, making this happen by relying on the entire capacity of its citizens. This design system was created to assist in storing data so that in the process adding data, searching for data, changing personnel data, recapping absences, leave, retirement, treatment, and promotions can be faster, more precise, safe, and easier to manage employee data. Using the waterfall method, it is hoped that the design of this personnel application can help speed up work in a structured manner and in accordance with user needs. In system design using MySQL as database storage and HTML, PHP, CSS as programming languages. The result of this design is a web-based employee data collection system that can provide employee data information and act as a safer place to store employee data.